Pengaruh Event ESMOD Fashion Festival 2012 terhadap citra ESMOD Jakarta - Rahayu, Sri (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2013)
The problem in this study is how much influence the ESMOD Fashion Festival 2012 Event on the image ESMODJakarta on students of SMK Negeri 30 Jakarta Department of dressmaking . The purpose of this study was to determinethe influence of ESMOD Fashion Festival 2012 Event on the image ESMOD Jakarta on students of SMKNegeri 30 Jakarta Department of dressmaking .Theory is used for solving the problem is the overlapping of Interest theory that explains the communicationprocess will run well when the communication between the actors involved much in common in terms of frame ofreference . Sources need to first recognize the characteristics of the individual , social and cultural rights of therecipient before he delivered the message to be conveyed . The second uses the model of Fishbein Multi Attributedescribing the event activities . Fishbein model explains the formation of attitudes in response to the attributes. Fishbein models showed that the attitude of an object depends on the probability that an object has certain attributesand the attributes diinginkanya level and at the level of the attributes desired . Confidence of the object isthen formed , because the attributes that exist at the object .This research is explanatory research, which aims to examine the effect of two variables: the independent variable( Event ESMOD Fashion Festival 2012 ) and the dependent variable ( Image ESMOD Jakarta ) . Samples takenare students of SMK Negeri 30 Jakarta as many as 30 of the student population of 30 students . Sampling basedon total sampling . Data were collected through questionnaires answered by the respondents , any answer in thequestionnaire that was answered by the respondents were given a score based on a Likert scale . The score sheetis inserted into the coding ( coding sheet ) . For purposes of data analysis techniques used Pearson Product Momentwith SPSS ( Statistical Package for Social Science ) .From the analysis of the coefficient of determination between the ESMOD Fashion Festival 2012 Event of theESMOD Jakarta Image obtained a value of 0.678 or 67.8 % . ESMOD Fashion Festival Event means to give effectto the image ESMOD Jakarta of 67.8 % , while the remaining 32.2 % is influenced by other factors .